1975
DOI: 10.1121/1.380479
|View full text |Cite
|
Sign up to set email alerts
|

Wave propagation in two−layered piezoelectric plates

Abstract: Wave propagation and thickness vibrations in two−layered piezoelectric plates are investigated by the three−dimensional theory of piezoelectricity and approximate theories. Piezoelectric materials of hexagonal symmetry are considered. The sixfold axes of the materials are assumed to be parallel or perpendicular to the plate. Dispersion curves and frequencies for thickness vibrations are presented. The electromechanical coupling effect is examined and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…(4) and (5) under the conditions (6)-(10). Based on the partial wave method [Cheng and Sun (1975)], the solution of Eq. (4) can be assumed as…”
Section: ( )mentioning
confidence: 99%
“…(4) and (5) under the conditions (6)-(10). Based on the partial wave method [Cheng and Sun (1975)], the solution of Eq. (4) can be assumed as…”
Section: ( )mentioning
confidence: 99%
“…The study of wave propagation inside piezoelectric materials attracted much attention for the application of delay line. The time delay effect was achieved when a piezoelectric element is used to transform the electrical signal into the elastic wave propagating through it [ 69 , 70 ]. Sun and Cheng [ 71 ] studied acoustic wave propagating around a piezoelectric cylinder with thin metallic overlay and showed that the wave propagation characteristics changed with different metallic layers.…”
Section: Analysis and Applications Of Piezoelectric Sensors And Actmentioning
confidence: 99%
“…Consider the free-wave propagation in the x 2 -direction, expressed in the form (Cheng & Sun 1975) u 2 = Ae ibkx 3 e ik(x 2 ¡vt) ; u 3 = Be ibkx3 e ik(x2¡vt) ; ¿ = Ce ibkx 3 e ik(x 2 ¡vt) ;…”
Section: (Ii) Governing Equations For Piezoelectric Layermentioning
confidence: 99%